A review on modular construction for high-rise buildings. (December 2020) - Thai, Huu-Tai; Ngo, Tuan; Uy, Brian
Abstract: Modular construction is considered as a game-changing technology since it offers faster construction, safer manufacturing, better quality control, and lower environmental impacts compared with the traditional onsite construction. These benefits can be maximised in high-rise buildings due to their inherently topological modular form and the increased number of repeatable modules. However, current applications of modular construction for high-rise buildings are very limited due to the lack of strong structural systems and joining techniques to ensure structural integrity, overall stability, and robustness of an entirely modular building. In addition, the unavailability of design guidelines also inhibits the construction industry in implementing such technology. With recent advancements in structural systems and materials, there is great potential for real world applications of modular construction in high-rise buildings. This paper presents a critical review of recent innovations in modular construction technology for high-rise buildings with an emphasis on structural systems, joining techniques, progressive collapse and structural robustness. The developments of design codes for modular construction are also discussed. The paper concludes by highlighting the technical challenges that hinder the widespread adoption of modular construction, and proposing potential solutions for future research. This review paper is expected to be a complete reference for experts, researchers and professionals in this field of study.